Predicting children's word-reading accuracy for common English words: The effect of word transparency and complexity. - Spencer, Ken (British Journal of Psychology, 2010)
The effects of printed word frequency and transparency measures on single word reading accuracy were examined in 105 six-year-old children. The results indicated that it may be necessary to re-appraise notions of orthography-to-phonology correspondences for children of this age. The influence of orthographic neighbourhood size appeared to derive from word frequency and graphemic complexity. The results also indicated that sonograph frequency was more predictive of reading accuracy than the GPC rules and weighted correspondences currently embodied in dual route and connectionist models of skilled reading.